Thermo-Mechanical Fatigue Behavior of Materials: Third Volume 2000
DOI: 10.1520/stp15257s
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical Out-of-Phase Fatigue Life of Overlay Coated IN-738LC Gas Turbine Material

Abstract: Thermomechanical fatigue (TMF) is a unique type of fatigue process in which a component is simultaneously subjected to fluctuating loads and temperature. Isothermal life prediction techniques are often not applicable to TMF conditions since mechanical properties are temperature dependent with different damage mechanisms. There are two major cycles in TMF: the in-phase (IP) cycle where the maximum strain peak coincides with the maximum temperature and the out-of-phase (OP) cycle where the maximum strain and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Zamrik and Renauld [93] proposed also an energy based approach in their lifetime model. The energy density is calculated by maximum stress r eq max and the strain amplitude T eq in the tensile range.…”
Section: The Plastic Energy Density W Plmentioning
confidence: 99%
See 2 more Smart Citations
“…Zamrik and Renauld [93] proposed also an energy based approach in their lifetime model. The energy density is calculated by maximum stress r eq max and the strain amplitude T eq in the tensile range.…”
Section: The Plastic Energy Density W Plmentioning
confidence: 99%
“…The energy density is normalized by ultimate tensile strength R m and the elongation at rupture A f . Thus, the damage parameter according to Zamrik and Renauld [93] DW Zam is given by Eq. (8).…”
Section: The Plastic Energy Density W Plmentioning
confidence: 99%
See 1 more Smart Citation
“…During the recent decades extensive research has been performed on the behavior of cast aluminum and iron alloys for internal combustion engines as well as on cast and wrought Nickel alloys for gas turbine applications, e.g. [9][10][11][12][13][14][15][16][17][18].…”
Section: Thermocyclic Loadingmentioning
confidence: 99%
“…However, since TMF tests are difficult to be performed only a few studies are available in the open literature [8][9][10][11][12][13]. Among the previous experiments, Kowalewski and Mughrabi [10] found that the out of phase (OP) TMF life of low pressure plasma spraying (LPPS) NiCrAlY coated directionally solidified nickel-based superalloy was shorter than that of the bare substrate.…”
Section: Introductionmentioning
confidence: 99%